Cyclodextrin facilitated electrospun chitosan nanofibers1. Issue 10 (6th February 2015) - Burns, Nancy A.; Burroughs, Michael C.; Gracz, Hanna; Pritchard, Cailean Q.; Brozena, Alexandra H.; Willoughby, Julie; Khan, Saad A.
<x xml:space="preserve">Abstract</x> Cyclodextrin complexation of chitosan presents a novel route to achieve nanofibers of chitosan and other difficult-to-electrospin biopolymers.